Activation Energy of SDS–Protein Complexes in Capillary Electrophoresis with Tetrahydroxyborate Cross-Linked Agarose Gels - Dániel Sárközy; András Guttman (Gels)
Hydrogels like agarose have long been used as sieving media for the electrophoresis-based analysis of biopolymers. During gelation, the individual agarose strands tend to form hydrogen-bond mediated double-helical structures, allowing thermal reversibility and adjustable pore sizes for molecular sieving applications. The addition of tetrahydroxyborate to the agarose matrix results in transitional chemical cross-linking, offering an additional pore size adjusting option. Separation of SDS-proteins during gel electrophoresis is an activated process defined by the interplay between viscosity, gelation/cross-link formation/distortion, and sample conformation. In this paper, the subunits of a therapeutic monoclonal antibody were separated by capillary SDS agarose gel electrophoresis at different temperatures. The viscosity of the separation matrix was also measured at all temperatures. In both instances, Arrhenius plots were used to obtain the activation energy values. It was counterintuitively found that larger SDS–protein complexes required lower activation energies while their low-molecular-weight counterparts needed higher activation energy for their electromigration through the sieving matrix. As a first approximation, we considered this phenomenon the result of the electric force-driven distortion of the millisecond range lifetime reticulations by the larger and consequently more heavily charged electromigrating molecules. In the meantime, the sieving properties of the gel were still maintained, i.e., they allowed for the size-based separation of the sample components, proving the existence of the reticulations. Information about the activation energy sheds light on the possible deformation of the sieving matrix and the solute molecules. In addition, the activation energy requirement study helped in optimizing the separation temperature, e.g., with our sample mixture, the highest resolution was obtained for the high-molecular-weight fragments, i.e., between the non-glycosylated heavy chain and heavy-chain subunits at 25 °C (lower Ea requirement), while 55 °C was optimal for the lower-molecular-weight light chain and non-glycosylated heavy chain pair (lower Ea requirement). Future research directions and possible applications are also proposed.